Environmental and Health Risk Assessment of Particulate Matter Associated with Dusty Football Field - Enetimi I. Seiyaboh; Tariwari C.N Angaye; Odangowei I. Ogidi (Journal of Experimental and Clinical Toxicology, 2019)
Over the decades there have been problems associated with Particulate Matter (PM) arising from anthropogenic activities. Evaluation and health risk assessment of PM associated with football field was carried out in 5 sampling locations, including the control station. Digital portable AEROCET 513 (Metone instrument) PM meter was used for the evaluation Results showed levels of PM for; PM1.0(13.73 – 20.18 µg/m3), PM2.5 (19.11 – 28.83 µg/m3), PM4.0 (24.73 – 44.63 µg/m3), PM7.0 (41.07 – 67.04 µg/m3), and PM10 ranging from 65.48 – 90.82 µg/m3. In addition, value of the control station was lowest amongst all recorded values of PM (p<0.05). Based on Air Quality Index evaluation, the football fields were predominantly rated as unhealthy, with other cases rates as; hazardous and unsafe for sensitive group. This investigation therefore concludes that the emission of PM from the football field are reflection of vehicular emissions and agitated dust particles. Hence mitigable measure must be applied without much ado, in order to ameliorate the daily chronic exposure to PM.
Keywords: Particulate matter